2010
DOI: 10.1111/j.1750-3639.2009.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and Its Receptor are Overexpressed in Brain Tumors and Correlate with the Degree of Malignancy

Abstract: Although leptin and its receptor (ObR) have emerged as important cancer biomarkers, the role of the leptin system in brain tumor development remains unknown.We screened 87 human brain tumor biopsies using immunohistochemistry and detected leptin and ObR in 55.2% and 60.9% cases, respectively. In contrast, leptin and ObR were absent in 14 samples of normal brain tissue. The presence of leptin correlated with ObR with overall concordance 80.5%. The leptin/ObR system was highly expressed in glioblastomas and anap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 74 publications
(129 reference statements)
3
51
1
Order By: Relevance
“…This study confirmed our previous findings that leptin stimulates several growth-related intracellular pathways and acts as a mitogen in GBM cells (20). Furthermore, we demonstrated for the first time that leptin activates migration in human GBM cells, which is consistent with the observation that the hormone induces migration of rat C6 glioma cells (22).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This study confirmed our previous findings that leptin stimulates several growth-related intracellular pathways and acts as a mitogen in GBM cells (20). Furthermore, we demonstrated for the first time that leptin activates migration in human GBM cells, which is consistent with the observation that the hormone induces migration of rat C6 glioma cells (22).…”
Section: Discussionsupporting
confidence: 80%
“…ObR-positive LN18 and LN229 glioblastoma cell lines were obtained from ATCC (Manassas, VA, USA). Both cell lines were cultured in low-glucose Dulbecco's modified Eagle's medium (DMEM) (Cellgro Mediatech, Manassas, VA, USA) supplemented with 5% fetal bovine serum (Cellgro Mediatech) as described in a previous study (20). The study was approved by the Biosafety Committee at Temple University, PA, USA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Diverse cancer cells derived from different tissues, such as brain, breast, colon or prostate, were reported to have ObR expression. [21][22][23][24][25] Furthermore, Ob-R overexpression not only correlated with the degree of malignancy, but also was an independent prognostic variable to predict poor progression-free survival in brain tumor, ovarian cancer, and breast cancer, 24,26,27 which suggested that ObR+ cells might be closely related with tumor initiation and development. In this study, we claimed that ObR+ glioblastoma cells presented chemoresistance, which showed that TMZ could not inhibit cell proliferation and could not induce apoptosis effectively.…”
Section: Discussionmentioning
confidence: 99%